A Study ofWork Life Balance and Job Satisfaction. - Kaur , Surjit; Mahajan, Pooja (Gyan Management Journal, 2017)
The purpose of conducting the study is to investigate the relationship between work life balance, and job satisfaction. The study has been undertaken among the private sector bank employees of tricity (Chandigarh- Mohali- Panchkula). Data was collected from 75 employees with the help of a questionnaire. Data has been analyzed through (SPSS). Descriptive Statistics, Correlation and Regression, t- test and ANO VA (One way) analysis has been applied to draw the results of the study The findings of the study indicate that there exit a positive correlation between work life balance and job satisfaction.